2021
DOI: 10.1108/sasbe-01-2021-0008
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing households' intention to adopt solar energy solutions in Zambia: insights from the theory of planned behaviour

Abstract: PurposeThis study examined the factors that influence households’ intention to adopt solar energy solutions in Zambia. This, in view of low adoption rates of solar energy solutions even in the wake of a widespread electricity power generation deficit across sub-Sahara Africa (SSA) has plagued the region with daily electricity load shedding lasting several hours at a time. Given the vast potential for solar energy generation in the region, solar energy solutions have become an attractive option to grid-based el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…The findings of [66] also demonstrated that buyers' buying decisions were established on a solid faith in the advantages of the specific thing they needed to buy. Likewise, another recent study in Zambia factors influencing households' intention to adopt solar energy solutions revealed that due to its numerous advantages and the region's vast solar energy generation potential, solar energy solutions have become an attractive alternative to grid-based electricity, and many households are influencing their adoption [123]. Consumers can adopt solar PV if they can see the real advantages of using it over non-renewable resources.…”
Section: Structural Model Testingmentioning
confidence: 99%
“…The findings of [66] also demonstrated that buyers' buying decisions were established on a solid faith in the advantages of the specific thing they needed to buy. Likewise, another recent study in Zambia factors influencing households' intention to adopt solar energy solutions revealed that due to its numerous advantages and the region's vast solar energy generation potential, solar energy solutions have become an attractive alternative to grid-based electricity, and many households are influencing their adoption [123]. Consumers can adopt solar PV if they can see the real advantages of using it over non-renewable resources.…”
Section: Structural Model Testingmentioning
confidence: 99%
“…Finally, the opinions of friends, family and other people that affect people’s behavior (subjective norms) influence behavior intentions, which supports H6 ( β = 0.236, t -values = 4.890, sig = 0.000). Alam et al (2021) and Zulu et al (2021) also indicated that if the customers find their “significant others” prefer solar NMS, they, too, will develop a positive attitude toward solar NMS. Figure 1 depicts the validated structural model showing the constructs, their relational flows and the beta values.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, individuals are influenced by the perception of others, and “subjective norms” positively affect behavioral intentions to adopt solar NMS. Thus, campaigns highlighting the adverse effects of conventional energy sources and the advantages of solar NMS can be organized (Zulu et al , 2021). Given the impact of PBC on behavioral intentions, the makers should supply additional knowledge, information and experience on how customers may readily get solar NMS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When someone believes that something is good, he/she will have the intention to pursue it. The theory of planned behavior is based on the assumption that someone's beliefs are influenced by the firm's climate and perceptions towards the firm behavior, considering that each worker is a member of the firm [30,31]. Previous experience as a member of the group may shape the person's intentional behavior.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%